A Smart Hoodie- Assistive Technology for Blind People Using IoT - et. al., Kathiravan M, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Assistive technology for the blind is a field of research that is gaining more and more importance due to the eruption of new interest from different fields. These research findings have had a huge social impact among elderly and blind population. In this paper, we introduced a novel Smart Hoodie which can sense the objects around them and can prevent the blind people from getting hurt accidentally or banging on heavy objects. The technology used here is IoT, where a Raspberry Pi kit is used along with ultrasonic sensors which can sense objects. A micro camera can be fixed on top of the Hoodie, which is triggered once the sensor detects the object and then object recognition is performed; a voice notification is generated either with the speaker or earphones. We can also track the location of a blind person in case they are lost, using a GPS module. A GSM module is used by a blind person to send messages in case of any emergency. Although, there were a lot of discoveries related to the above-mentioned issue, it has inflamed that our invention is much better than other state of the art approaches.